Audit Judgment with Emotional Intelligence as Moderation Variable in BPKP Bali - Ni Putu Shinta Dewi; Ni Komang Kris Muliartini; Ni Wayan Rustiarini (AFEBI Accounting Review, 2021)
This study aims to analyze the effect of obedience pressure, time budget pressure and task complexity on audit judgment with emotional intelligence as a moderating variable in BPKP Bali Province. The population of this research is auditors who work at BPKP Bali Province. The sample in this study were 68 respondents who were determined based on the saturated sampling method. The results showed that obedience pressure had no effect on audit judgment, time budget pressure and task complexity had a negative effect on audit judgment, emotional intelligence had a positive effect on audit judgment, emotional intelligence strengthened the relationship between obedience pressure and time budget pressure and emotional intelligence was unable to moderate the relationship complexity duty against audit judgment